GABAB receptors: modulation of thalamocortical dynamics and synaptic plasticity. (21st February 2021) - Sanchez-Vives, Maria V.; Barbero-Castillo, Almudena; Perez-Zabalza, Maria; Reig, Ramon
Highlights: GABAB -Rs can be pre or postsynaptic, inhibiting both excitatory and inhibitory neurons, and also decreasing excitation. Activation of GABAB -Rs in the thalamus and cortex modulates emergent rhythms and synaptic plasticity. In the thalamus, activation of GABAB -Rs switches the network from generating spindle waves to spike-and-wave cycles. During cortical Up and Down states, GABAB -R blockade consistently elongates Up states and modifies the rhythmic cycle. Blockade of GABAB -Rs increases regularity of the cycle and decreases the network complexity of causal interactions. Abstract: GABAB -receptors (GABAB -Rs) are metabotropic, G protein-coupled receptors for the neurotransmitter GABA. Their activation induces slow inhibitory control of the neuronal excitability mediated by pre- and postsynaptic inhibition. Presynaptically GABAB -Rs reduce GABA and glutamate release inhibiting presynaptic Ca 2+ channels in both inhibitory and excitatory synapses while postsynaptic GABAB -Rs induce robust slow hyperpolarization by the activation of K + channels. GABAB -Rs are activated by non-synaptic or volume transmission, which requires high levels of GABA release, either by the simultaneous discharge of GABAergic interneurons or very intense discharges in the thalamus or by means of the activation of a neurogliaform interneurons in the cortex. The main receptor subunits GABAB 1a, GABAB 1b and GABAB 2 are strongly expressed in neurons and glial cells throughout the central nervous system and GABAB -R activation is related to many neuronal processes such as the modulation of rhythmic activity in several brain regions. In the thalamus, GABAB -Rs modulate the generation of the main thalamic rhythm, spindle waves. In the cerebral cortex, GABAB -Rs also modulate the most prominent emergent oscillatory activity—slow oscillations—as well as faster oscillations like gamma frequency. Further, recent studies evaluating the complexity expressed by the cortical network, a parameter associated with consciousness levels, have found that GABAB -Rs enhance this complexity, while their blockade decreases it. This review summarizes the current results on how the activation of GABAB -Rs affects the interchange of information between brain areas by controlling rhythmicity as well as synaptic plasticity.